Study the Relationship Between Organisational Environment of Mumbai Colleges And Exchange Of Data & Information among Teaching Staff for the Practice of Knowledge Management - Gala, Shaili V. (SFIMAR Research Review, 2017)
Education is closely related with Knowledge Management (KM). Higher education institutions (HEIs) have significant opportunities to apply KM practices to support every part of their mission. KM can be used to support educational administration, which in turn supports teaching and learning. Educational administrators and teachers have begun to look at how they might use information systems to assist in creating effective learning environments. The practice of KM mainly depends upon the following factors: Organizational Climate, organizational culture, organizational leadership, climate for exchanging data etc. This paper tries to find out the relationship between the organizational environment and exchange of data for the practice of KM. Mumbai district was divided into six zones. Arts and Commerce colleges of Mumbai were taken as population for the study and from 74 colleges' primary data was collected. 712 responses were analyzed using SPSS package.